The effect of video modeling and tell-show-do on anxiety during dental radiographic examinations among children - Tania, Laura; Yanuaryska, Ryna Dwi; Wardani, Putri Kusuma (Majalah Kedokteran Gigi Indonesia, 2025)
Dental procedure anxiety refers to the fear experienced before and during dental treatment. To reduce anxiety levels in children undergoing radiographic examinations, non-pharmacological behavioral management techniques such as tell-show-do and modeling can be employed. This study aimed to compare the effectiveness of video modeling and the tell-show-do technique in reducing anxiety in children aged 5–7 years undergoing dental radiographic examinations at RSGM Prof. Soedomo, UGM. This quantitative study used a pretest–posttest control group design. The participants were children aged 5–7 years who underwent radiographic examinations at the Radiology Department of RSGM Prof. Soedomo, UGM, between September and December 2023. The sample was divided into three groups: Group A received the video modeling intervention, Group B received the tell-show-do intervention, and Group C served as the control group. Data were collected using the Modified Dental Anxiety Scale (MDAS) questionnaire and physiological anxiety measurements (blood pressure and pulse rate) using an Omron HEM-6161 digital tensiometer. MDAS scores were analyzed using the Kruskal-Wallis test, while blood pressure and pulse rate were analyzed using one-way ANOVA. A total of 146 participants were included. Significant differences were observed in MDAS scores, blood pressure, and pulse rate from pretest to posttest among all groups (p < 0.05). The tell-show-do group showed the greatest reduction in anxiety (3.74 ± 2.62), followed by the video modeling group (3.33 ± 2.30), and the control group (0.92 ± 2.33). Both the tell-show-do technique and video modeling are effective in reducing dental anxiety in children aged 5–7 years undergoing radiographic examinations at RSGM Prof. Soedomo, UGM.